AVAILABILITY OF PHYSICAL AND INSTRUCTIONAL FACILITIES AND ITS IMPACT ON STUDENT LEARNING OUTCOME IN PUBLIC SECONDARY SCHOOLS IN OGUN STATE, NIGERIA - David Esther C.; Emunemu B.O.; Emunemu B.O. (African Journal of Educational Management, 2021)
The study examined the availability of physical and instructional facilities and its impact on student learning outcome in public secondary schools in Ogun State, Nigeria. The study adopted the descriptive survey design. Purposive sampling was used to select four hundred and fifty-five students from senior secondary class two in the three senatorial districts in the state. Questionnaires, checklists and achievement tests were used as instrument. The hypotheses were analyzed using Pearson Product Moment Correlation for hypotheses (1) and (2) and Multiple Regression was used to test hypothesis (3). The findings of the study revealed that there was no significant relationship between availability of physical facility and student learning outcome in Mathematics (r=. -049, P>0.05), in English (r=. -081, P>0.05) and students learning outcome in behavior (r=.042, P>0.05). There was no significant relationship between availability of instructional facilities and students’ learning outcome in Mathematics (r=.039, P>0.05), in English (r=.052, P>0.05) and students learning outcome in behavior (r=.063, P>0.05). The Multiple Regression analysis showed that none of the independent variables significantly contributed to student learning outcome. The study concluded that poor academic achievement could have been worse without the availability of the physical and instructional facilities in the schools, Therefore, the government, other stakeholders and the school management should ensure that physical and instructional facilities are provided in such a way that they are up-to-date and appealing to the students so as to have a visible impact on the students learning outcome.